Effect of cooperative learning method Jigsaw type to learning motivation and learning outcome in student - Zulfikar Muhammad (University of Muhammadiyah Malang, 2018)
Each educational unit has a system to produce qualified graduates. Higher education system in Indonesia has four main stages namely input, process, output and outcomes. To produce quality outcomes, it is necessary to improve the learning process. One of the efforts to improve the learning process is by using the method of learning in accordance with the Competency Based Curriculum that is cooperative learning method, one of these methods that can be applied is cooperative learning method jigsaw. The purpose of this study is to determine the effect of jigsaw cooperative learning methods on motivation and student learning outcomes in Diploma Program Nursing of STIKes Kepanjen. This research method using quantitative method with quasi experimental design with pre-test-post-test, statistical test used is paired sample t-test. The results of this study indicate that the provision of learning methods using cooperative type Jigsaw can affect student motivation and learning outcomes